Penerapan Latihan Rom Aktif Terhadap Activity Daily Living (ADL) Dan Kekuatan Otot Pada Pasien Stroke Non Hemoragik Di RSUD Dr. Soebarkat Tjitrodarmodjo - Samalina Johana Ravensca Selwur; Niken Sukesi (Journal of Innovation Research and Knowledge, 2026)
Background: Non-hemorrhagic stroke is one of the leading causes of disability worldwide, resulting in muscle weakness and physical mobility impairment, which reduces patients' ability to perform Activities of Daily Living (ADL) independently. Active Range of Motion (ROM) exercise is a nonpharmacological nursing intervention that can be applied to improve muscle strength and ADL ability in non-hemorrhagic stroke patients. Objective: To determine the application of active Range of Motion (ROM) exercise on the improvement of muscle strength and Activities of Daily Living (ADL) ability in non-hemorrhagic stroke patients at Dr. Soebarkat Tjitrodarmodjo Hospital. Method: This study used a descriptive case study design involving 5 non-hemorrhagic stroke patients with muscle weakness and physical mobility impairment at Dr. Soebarkat Tjitrodarmodjo Hospital. Active ROM exercise was given once daily for approximately 30 minutes over 3 consecutive days according to the Standard Operating Procedure (SOP). Data were collected through structured clinical observation, using the Manual Muscle Testing (MMT) scale for muscle strength and the Barthel Index for Activities of Daily Living (ADL). Results: Before active ROM exercise was given, all respondents experienced muscle weakness with MMT scale 2-3 and a moderate to severe dependency category based on the Barthel Index. After 3 consecutive days of active ROM exercise, 4 of 5 respondents (80%) showed an increase in muscle strength scale and Barthel Index score, with a change in dependency category from severe to moderate or from moderate to mild, while 1 respondent (20%) did not show a significant improvement in muscle strength. Conclusion: Active ROM exercise has been proven to be applicable as an effective nonpharmacological nursing intervention in improving muscle strength and Activities of Daily Living (ADL) ability in most non-hemorrhagic stroke patients, although the magnitude of improvement achieved is individual and influenced by age, comorbidities, and the severity of the stroke.